PENGARUH WORK ETHICS TERHADAP KINERJA KARYAWAN DENGAN WORK LIFE BALANCE SEBAGAI VARIABEL INTERVENING PADA PT POS INDONESIA CABANG KEBONROJO SURABAYA - Alan, Nikolaus; Tandiyono, Tan Evan (GEMAH RIPAH: Jurnal Bisnis, 2025)
PT. Pos Indonesia, which is one of the State-Owned Enterprises (SOEs) engaged in the service sector, is required to innovate in order to meet the demands of improving the quality of services to the community. The purpose of the research to be achieved is in accordance with the formulation of the problem that has been described above to know, analyze and answer the role of work ethics on employee performance with work life balance as an intervening variable at PT Pos Indonesia. The population in this study is employees of PT Pos Indonesia Kebonrojo Surabaya branch. For the population of employees of PT. Pos Indonesia Kebonrojo Surabaya branch totals 150 people. This study uses a quantitative approacher because the data used is in the form of a questionnaire, the respondents of this study are employees of PT. Pos Indonesia branch Kebonrojo Surabaya sample that will be taken as many as 60 employees. Based on the results of the study, it is known that the fourth hypothesis tested in this study, namely "Work ethics have a significant effect on employee performance with work life balance as an intervening variable at PT Pos Indonesia" has proven to have a significant effect. This is evidenced by the results of the t-test which shows a significance value of 0.000 which is smaller than 0.05. Encourage and strengthen work ethics through training, coaching, and example from leaders.